Effect of Fibre Orientations and Nanosilica on Mechanical Properties and Ultimate Tensile Strength of Polymer Composite Materials - Jamaliah Md Said; Aidah Jumahat; Jamaluddin Mahmud (International Journal of Integrated Engineering, 2025)
Polymer composite materials have extensively been utilised due to their superior mechanical properties. Incorporating nanosilica into the resin matrix has been demonstrated to further enhance these properties. This study investigates the ultimate tensile strength of composites made with both pure (PW) and nanosilica-enhanced Willkat resin (5NSW), examining different fibre configurations oriented at 0° and 90°. Results show that the combination of 5 wt.% nanosilica (5NSW) provides the best tensile strength properties. Increasing the nanosilica content beyond this level results in higher viscosity and agglomeration, which adversely affect the properties. Basalt (B/B) comingle fibre exhibits the highest ultimate tensile strength with 302.46 MPa, followed by glass (G/G) comingle fibre with 137.69 MPa, with the addition of 5 wt.% nanosilica. The lowest strength is obtained with Arenga pinnata (AP/AP) fibres at 25.85 MPa in 0° fibre orientation; meanwhile, it increases in strength when hybridised with basalt and glass fibres. The orientation of the fibre also has an impact on the properties of the composite, where 0° fibre orientation gives a better value than 90° fibre orientation. Additionally, the incorporation of nanosilica into the matrix enhances the overall strength of the composites.